MOTIVASI TIONGKOK MENOLAK MEKANISME PENGURANGAN EMISI GAS KARBON DALAM THE DOHA CLIMATE GATEWAY TAHUN 2012 - Yudho Prasetyo; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes the motivation of Tiongkok rejected the emision trading in Doha Climate Gateway in 2012. Nowdays the climate changes are one of important issue in internationla relations Kyoto Protocoll are a diplomacy arround to tell about the climate change with some steps are joint implementations, emision trading and carbon mechanism.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the motivation of Tiongkok rejected the emision trading in Doha Climate Gateway. The theories applied in this research are decisions making policy theory by Graham T. Allison and national interest concept from Donald E. Nuchterlain.The research shows that the motivation of Tiongkok rejected the emision trading in Doha Climate Gateway cause some factors are disadvantages for national interest of Tiongkok, increase of emision carbon in the world and disadvantage for Tiongkoj indutrialization and some state of Kyoto Protocoll member notyet dealling about the emision trading.Key words: motivation, reject, emision and trade.